Quantitative evaluation of oculomotor disturbances in progressive supranuclear palsy. (April 2021) - Pagonabarraga, Javier; Horta-Barba, Andrea; Busteed, Laura; Bejr-kasem, Helena; Illán-Gala, Ignacio; Aracil-Bolaños, Ignacio; Marín-Lahoz, Juan; Pascual-Sedano, Berta; Pérez, Jesús; Campolongo, Antonia; Izquierdo, Cristina; Martinez-Horta, Saul; et al.
Abstract: Objectives: To explore and quantify systematically the ocular abnormal movements present in progressive supranuclear palsy (PSP) from the early stages, to assess the ability of this standardized examination in the differential diagnosis of PSP from Parkinson's disease (PD), and to compare in more detail oculomotor disturbances between PSP variants. Methods: Sixty-five consecutive PSP patients with <5 years of disease duration diagnosed according to MDS-PSP criteria, 25 PD patients and 25 controls comparable in age, education and disease duration were explored using a bedside battery of tests for the quantitative evaluation of oculomotor dysfunction in clinical practice. Other accepted scales were used for measurement of motor (PSPRS), cognitive (FAB) and behavioral (FBI) impairment. Results: Measurement of oculomotor dysfunction significantly differentiated PSP from PD and controls (p < 0.001) and showed high accuracy in the differential diagnosis of early-to-mid stage PSP from PD. PSP-Parkinsonism and PSP-Progressive Gait Freezing phenotypes showed more preserved ocular motor function compared to PSP-Richardson Syndrome, although no differences were found between PSP subtypes in the number of square wave jerks, optokinetic nystagmus defects, degree of apraxia of eyelid opening, or presence of the "Round the Houses" sign. Conclusions: Using a bedside clinical instrument for quantifying oculomotor disturbances in PSP shows promising potential at differentiating PSP from PD, and it seems able to provide a qualitative and quantitative description of ocular motor function in parkinsonian disorders. Highlights: To quantify oculomotor dysfunction in clinical practice shows promising potential at differentiating early PSP from PD. The measurement of oculomotor defects in PSP quantifies subtle signs in patients with and without supranuclear gaze palsy. No major differences were found between PSP subtypes in the presence of subtle oculomotor defects.